Pemanfaatan LKPD Interaktif Berbasis Liveworksheet untuk Meningkatkan Hasil Belajar Kognitif Muatan IPA Peserta Didik Kelas V di SD Negeri Jajar Kota Surakarta - Idam Ragil Widianto Atmojo; Matsuri Matsuri; Fadhil Purnama Adi; Roy Ardiansyah; Dwi Yuniasih Saputri (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this service activity is to describe the use of interactive Student Worksheets (LKPD) with live worksheets as an effort to improve the cognitive aspects of learning outcomes for fifth-grade elementary school students on science content. This service activity is carried out in SD Negeri Jajar class V with a total of 22 students. The method used in this service program is the Asset-based Community Development (ABCD) approach which is carried out in three stages. Data collection techniques used test, observation, interview, and document studies. The results of this activity indicate that the first stage, second stage, and third stage increased initially. The average students who completed the KKM in stage I was 63 to 73 in stage II and 95 in stage II. Thus, it can be concluded that the cognitive learning outcomes of fifth-grade students through the use of interactive LKPD with live worksheets on the science content at SD Negeri Jajar, Surakarta City have increased.